ENGLISH MOVIES AS A MOTIVATIONAL TOOL IN ENHANCING STUDENTS' LISTENING SKILLS - Ananda, Anisa Rizky; Pratolo, Bambang Widi (Universitas Muhammadiyah Metro, 2024)
Movies have been examined as one of the most exciting media that can help students learn listening skills. However, there is limited study on using English movies to enhance students' motivation in listening skills. This research aimed to determine students' perceptions of using movies as a motivational tool in enhancing students' listening skills. This research used qualitative study. The subjects of this study were 31 eleventh-grade students of class BP A at SMK Muhammadiyah Prambanan, Yogyakarta. In collecting data, the researchers used semi-structured interviews where open-ended questions allowed the researchers to freely ask the students and a questionnaire comprising ten items related to students’ responses regarding their motivation in learning to listen. Researchers prepared and organized research data for analysis, which involved compiling and organizing recordings into transcripts and participant observation notes. Most students showed that they were more interested and motivated in learning to listen to English movies. The students felt fun, interested, enjoyed, and more focused during the learning process. They got new vocabulary and understood what was being said in the movies. Pedagogically, this study implies that teachers should consider attractive learning media, especially for teaching listening, to enhance students’ motivation and interest in learning English.